Closing gaps in medication taking for secondary prevention of coronary heart disease patients among US adults. Issue 11 (November 2022) - Liu, Xiaowei; Tang, Lijiang; Tang, Ying; Du, Changqing; Chen, Xiaofeng; Xu, Cheng; Yan, Jing
Abstract: Background: The secondary preventive medical remedies used in the U.S. general population, particularly those with numerous co-morbidities, are poorly understood. We aimed to assess health outcomes and the extent of their adherence to guideline-based secondary prevention medications among U.S. coronary heart disease (CHD) patients. Methods: We analysed information from the U.S. National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018 on people in the United States aged 18 to 85 who had a personal history of coronary heart disease (CHD). Logistic regression analyses were used to identify characteristics related to healthcare access that were linked with not taking any indicated drugs among CHD and other co-morbidity patients in the U.S. Results: We gathered 4256 CHD patients aged 18 and above. Angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEIs/ARBs), statins, and antiplatelet medications were taken by 50.94%, 48.26%, 53.41 %, and 19.78% of the population, respectively. Surprising, not received recommended drugs was reached up to 21.12%, and taking all four drugs was only 7.64%. In conclusion, the logistic regression analysis revealed that the chance of not taking prescribed drugs increased with age (18–39), race (Hispanic and Non-Hispanic Black), low income, lack of insurance, and the absence of co-morbidities (hypertension, heart failure, and diabetes mellitus). Conclusions: The gap between the proposed secondary preventative measures and their actual execution remains sizable. In order to achieve 'Healthy Aging', a systematic approach for prevention of CHD is urgently needed. Abstract : Coronary heart disease; Secondary prevention; Medications; Co-morbidities.